Numerical simulations and case studies using visual C++ .NET (John Wiley & Sons, 2005)
Master the numerical simulation process required to design, test and support mobile and parallel computing systems. An accompanying ftp site contains all the Visual C++ based programs discussed in the text to help readers create their own programs. With its focus on problems and solutions, this is an excellent text for upper-level undergraduate and graduate students, and a must-have reference for researchers and professionals in the field of simulations.